2020
DOI: 10.3390/s20092582
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically-Induced Long-Period Fiber Gratings Using Laminated Plates

Abstract: This work presents a formation method of mechanically-induced long-period fiber gratings using laminated plates. The mechanically-induced long-period fiber grating is temporarily inscribed by compressing the optical fiber between a flat plate and the proposed laminated plate. In turn, the new laminated plate consists of a parallel assembling of single-edged utility blades. We present the experimental characterization of mechanically-induced long-period fiber gratings while employing three laminated plates with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…LPFGs with this number of the rejection bands and their spectral side lobes limit the wavelength-division multiplexing of LPFGs in cascade [16]. However, in the last years, it has been shown that LPFGs with a primary rejection band over a wide wavelength range using different inscription techniques is feasible [23][24][25][26][27]. Long-period fiber gratings with a primary rejection band facilitate the deployment of fiber optic distributed sensing systems based on the wavelength-division multiplexing of LPFGs.…”
Section: Lpfgs Principlementioning
confidence: 99%
See 2 more Smart Citations
“…LPFGs with this number of the rejection bands and their spectral side lobes limit the wavelength-division multiplexing of LPFGs in cascade [16]. However, in the last years, it has been shown that LPFGs with a primary rejection band over a wide wavelength range using different inscription techniques is feasible [23][24][25][26][27]. Long-period fiber gratings with a primary rejection band facilitate the deployment of fiber optic distributed sensing systems based on the wavelength-division multiplexing of LPFGs.…”
Section: Lpfgs Principlementioning
confidence: 99%
“…The MI-LPFG can be achieved when the optical fiber is compressed between a flat aluminum plate and a laminated plate, see Figure 1b. The laminated plate consisted of a parallel assembling of single-edged utility blades [23]. The laminated plate had a length of approximately 30 mm, an average period of 490 ± 10 µ m, and an average duty cycle of the refractive-index modulation of 0.2.…”
Section: Setup and Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ]. LPGs have been fabricated with a variety of techniques, such as irradiation through: UV laser [ 1 ], CO 2 laser [ 6 ], and femtosecond laser [ 7 ]; electric arc discharge [ 8 , 9 ]; mechanically induced by pressing a periodically grooved plate on a fiber [ 10 , 11 , 12 ] using machined metallic or silica plates [ 10 ], v-grooves on a tube [ 13 ]; coil spring [ 14 ], and recently, pilling of blades [ 15 ], and 3D printing of amplitude masks [ 11 , 12 ]; ion implantation [ 16 ]; and periodical etching of the fiber cladding to produce a corrugated structure [ 17 ]. Among those, the CO 2 and the UV laser inscription have been one of the most used.…”
Section: Introductionmentioning
confidence: 99%
“…Among those sensors, long-period fiber grating (LPG) guides the core lightwave to outer cladding region via a longitudinal index modulation structure with a period of hundreds of microns to millimeters, allowing light to interplay further with the ambient medium. The LPG outperforms its counterparts lying in the combination of ease of fabrication, the flexibility of design, the abundance of serviceable signals, cost-effectiveness, and high sensitivity [ 15 , 16 , 17 ]. As a consequence, the LPG refractometer is soon considered as a competitive approach for label-free and in-situ assessing biological and chemical targets in which the molecular reaction events could be transduced simply by the grating resonance shift.…”
Section: Introductionmentioning
confidence: 99%